2022
DOI: 10.1101/2022.07.06.499010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NAD+repletion with niacin counteracts cancer cachexia

Abstract: Cachexia is a debilitating wasting syndrome and highly prevalent comorbidity in cancer patients. It manifests especially with energy and mitochondrial metabolism aberrations that promote tissue wasting. We recently identified nicotinamide adenine dinucleotide (NAD+) loss to associate with muscle mitochondrial dysfunction in cancer hosts. In this study we confirmed that depletion of NAD+ and downregulation of Nrk2, an NAD+ biosynthetic enzyme, are common features of different mouse models and cachectic cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Interestingly, in mouse models of cancer cachexia muscle NAD deficiency and alterations in NAD biosynthesis were observed with consequent decline in mitochondrial oxidative phosphorylation [15]. Another recent study demonstrated in mouse models of cancer cachexia that the NAD+ deficiency may be counteracted by the administration of Niacin (vitamin B3) [8 ▪ ]. The supplementation of Niacin was also able to improve mitochondrial metabolism and cancer cachexia [8 ▪ ].…”
Section: Kynurenine Pathway and Muscle Metabolism During Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in mouse models of cancer cachexia muscle NAD deficiency and alterations in NAD biosynthesis were observed with consequent decline in mitochondrial oxidative phosphorylation [15]. Another recent study demonstrated in mouse models of cancer cachexia that the NAD+ deficiency may be counteracted by the administration of Niacin (vitamin B3) [8 ▪ ]. The supplementation of Niacin was also able to improve mitochondrial metabolism and cancer cachexia [8 ▪ ].…”
Section: Kynurenine Pathway and Muscle Metabolism During Cancermentioning
confidence: 99%
“…Another recent study demonstrated in mouse models of cancer cachexia that the NAD+ deficiency may be counteracted by the administration of Niacin (vitamin B3) [8 ▪ ]. The supplementation of Niacin was also able to improve mitochondrial metabolism and cancer cachexia [8 ▪ ]. In this light, it may be interesting to elucidate the role of Kyn metabolism in promoting NAD+ deficiency in muscle during cancer and if targeting this pathway may promote muscle mass preservation in animal models of cancer cachexia.…”
Section: Kynurenine Pathway and Muscle Metabolism During Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Beltrà et al 21 found that in the face of cachexia, a high‐incidence complication of malignant tumors, vitamin B3 niacin (NAD + precursor) repletion can effectively correct cellular NAD + levels, thereby counteracting tumor cachexia and improving long‐term prognosis. Furthermore, nicotinamide (the active amide existence of vitamin B3) is also one precursor of NAD + as well as has been shown to modulate the TIME in breast cancer, 19 enhance sensitivity to radiotherapy in bladder cancer, 22 and stimulate the p53/miR‐34a/Sirt1/p53 axis for promoting apoptosis in chronic lymphocytic leukemia 23 .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Based on this, a variety of genes or enzymes with dysregulated expression involved in the sustained production of NAD + in malignant tumors have been shown to be good prognostic indicators and are being further explored for their therapeutic potential as targets for the corresponding antitumor drugs. 20 Specifically, Beltrà et al 21 found that in the face of cachexia, a highincidence complication of malignant tumors, vitamin B3 niacin (NAD + precursor) repletion can effectively correct cellular NAD + levels, thereby counteracting tumor cachexia and improving long-term prognosis. Furthermore, nicotinamide (the active amide existence of vitamin B3) is also one precursor of NAD + as well as has been shown to modulate the TIME in breast cancer, 19 enhance sensitivity to radiotherapy in bladder cancer, 22 and stimulate the p53/miR-34a/Sirt1/p53 axis for promoting apoptosis in chronic lymphocytic leukemia.…”
mentioning
confidence: 99%